2012
DOI: 10.1097/sla.0b013e31825b6cb1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Usefulness of Breast CT Imaging in Delineating Tumor Extent and Guiding Surgical Management

Abstract: This prospective study suggests that breast CT, carried out in the supine position, is useful in the preoperative determination of the optimal surgical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Our study demonstrated that PC-CT has a higher diagnostic significance in detecting adjacent DCIS compared with DM. Our PC-CT data align with prior studies, supporting the notion that CT could be a valuable imaging tool for detecting DCIS 15,24,25 . The relatively poor performance of DM in our study can be explained by the fact that only 5/12 cases (42%) with peritumoral DCIS exhibited calcifications.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study demonstrated that PC-CT has a higher diagnostic significance in detecting adjacent DCIS compared with DM. Our PC-CT data align with prior studies, supporting the notion that CT could be a valuable imaging tool for detecting DCIS 15,24,25 . The relatively poor performance of DM in our study can be explained by the fact that only 5/12 cases (42%) with peritumoral DCIS exhibited calcifications.…”
Section: Discussionsupporting
confidence: 87%
“…Our PC-CT data align with prior studies, supporting the notion that CT could be a valuable imaging tool for detecting DCIS. 15,24,25 The relatively poor performance of DM in our study can be explained by the fact that only 5/12 cases (42%) with peritumoral DCIS exhibited calcifications. This percentage is relatively low compared with other cohorts.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, the comprehensive assessment of multiple sequence images can enhance the accuracy of tumor invasion prediction and ultimately improve the success rate of BCS. Breast MRI exhibits a sensitivity of over 90% in detecting invasive breast cancer[ 33 - 37 ]. The American College of Radiology has classified the morphology and characteristics of lesions in detail in the BI-RADS MR system[ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…CECT remains a cost-effective means to assess the status of axillary lymph nodes among patients with breast cancer despite the progress of positron emission tomography/computed tomography (PET/CT) and magnetic resonance imaging (MRI) [16, 17]. Beginning in January 2008, most surgeons in our institution gradually adopted preoperative CECT for assessment of axillary lymph nodes.…”
Section: Discussionmentioning
confidence: 99%